Traditional play and contemporary curriculum : parents' and teachers opinions - Visković, Ivana (Array, 2020)
Changes in social interactions in contemporary society limit the transmission of the traditional play as a significant segment of cultural intangible heritage. It is assumed that the introduction of the traditional play in the institutional Early Childhood Education and Care (ECEC) would contribute to its preservation.The opinions of teachers and parents of children of early and preschool age on the importance and purposefulness of the application of traditional play in the educational process were examined.The importance of traditional play was assessed more significantly by participants of older than younger age, and those highly educated than those less educated.The place where the participants grew up was related to the assessment of the limitations of the traditional play. Assessing outdoor play without adult supervision positively correlates with assessing children’s preoccupation with the virtual world. Conducting action research on the possibility of implementing traditional play, along with longitudinal research on children’s development, could possibly indicate the importance of traditional play.